Rural tourism as a component of the innovative potential of Ukrainian rural areas - Hotra, Viktoriya; Ihnatko, Mariia; Serzhanov, Vitaliy; Andriyiv, Nataliya (<center>Conference Proceedings Determinants Of Regional Development</center>; No 2 (2021): Conference Proceedings - VIII International Scientific Conference Determinants of Regional Development, 2021)
Given the rich tourist and recreational resources of Ukraine, it is the development of tourism that should be considered as one of the ways to solve economic, social, and environmental problems. However, the available resource potential is not rationally used, so the study of innovative development prospects of rural tourism is extremely relevant. The article under consideration aims at the analysis of a state of rural tourism as an advanced innovative direction for strengthening of socio-economic development of rural areas by analyzing the level of development of rural tourism in the regions of Ukraine. The objective of the study is rural tourism. The article also casts light upon the evaluative peculiarities of the current level of development of regional tourist - recreational complexes. The notion of a category «innovation potential of a region» has been defined and structurally described. Peculiarities of attractiveness of Ukraine’s regions have been determined. The level of development of tourism sector has been fundamentally estimated. Precise mechanisms for promotion of development of rural tourism by foreign countries have been provided. There have been singled out the following problems influencing the development of rural tourism in rural areas of Ukraine: poor auto-transport system, lack of access to Internet, insufficient marketing policy, strong competition with foreign businesses. The time scope in the analysis refers to the period 2018-2020. The following research methods are used in the article: dialectical, monographic, comparison, graphic, statistical analysis, method of integrated indicators construction, abstract-logical, economic modeling. The analysis showed that Ukraine has all the necessary resources for the development of rural tourism. The most promising areas for this type of tourism are Vinnytsia, Volyn, Zakarpattia, Ternopil and Ivano-Frankivsk regions.